Perlindungan Hukum Lingkungan Terhadap Dampak Perilaku Masyarakat Yang Membuang Sampah Di Sungai - Putu Ary Prasetya Ningrum (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
The problem of waste is a social phenomenon that needs attention from all parties, because every human being must produce waste. Environmental cleanliness is not only the responsibility of the government, but it is hoped that the participation of all elements of society, to participate in maintaining environmental cleanliness and to separate each household. The government in exercising its authority and obligation to enforce environmental law can be carried out through supervision and the application of legal sanctions. One form of its business is in the form of stipulating statutory regulations or laws in the environmental sector, both at national and regional scales